Content-centric storage: accessing data objects based on metadata and relationships - Jaeger, Michael C.; Messina, Alberto; Lorenz, Mirko (Content-centric storage: metoda udostępniania obiektów poprzez metadane i relacje, 2012)
Emerging storage cloud environments aim at facilitating the storage, retrieval, association, analysis and distribution of data and content with one of the fastest growing content types being fixed content (also known as object storage). Fixed content often has rich, structured and mutable metadata, which enables finding, managing and extracting value from the content as well as providing information regarding the meaning of the object and its relationship to other objects. In this paper we introduce an approach, namely content-centric storage, which allows applications to access data objects through information about their content rather than their path in a hierarchical structure. The applications do not need any knowledge about the data store organization or the place in a storage hierarchy. Rather, the applications may query for the desired content based on metadata associated with the data objects. We also demonstrate the operation of the implemented approach and evaluate its effectiveness using a real-world scenario, based on a media production application
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 38-60
Keywords: cloud storage; content-centric; metadata; data modeling; object storage; distributed systems; server applications; przechowywanie w chmurze; dostęp do obiektów sterowany zawartością; metadane; modelowanie danych; przechowywanie obiektów; systemy rozproszone